2002
DOI: 10.1038/sj.leu.2402772
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of acute myeloid leukemia following intensive therapy for AML – relapse, secondary disease or bad luck?

Abstract: Figure 1R-banded karyotype showing the paracentric inversion of chromosome 16 and double trisomies 9 and 22. diagnosis, as the bone marrow is not involved. 3,4 Our patient had a diagnosis of lymphoma before recognizing that it was a GS.Cytogenetic analysis of AML patients with chloroma have rarely been reported in the literature. However, it appears that patients with t(8;21)-associated AML type 2 are more prone than others to develop GS. Indeed, 4.5 to 38% of patients with t(8;21)(q22;q22) developed GS. 1,5 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…This case is characterized by a longer latency period than in previous reports of secondary AML following hematologic and/or non hematologic malignancies [2,3] as well as rare cases of secondary AML following de novo AML [5,6], in the setting of an allograft. In our case, the new complex cytogenetic aberrations, as well as the allograft setting, suggested that the origin of the second AML might be biologically unrelated to the first.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…This case is characterized by a longer latency period than in previous reports of secondary AML following hematologic and/or non hematologic malignancies [2,3] as well as rare cases of secondary AML following de novo AML [5,6], in the setting of an allograft. In our case, the new complex cytogenetic aberrations, as well as the allograft setting, suggested that the origin of the second AML might be biologically unrelated to the first.…”
Section: Discussionmentioning
confidence: 91%
“…Secondary AML is primarily associated with therapy-related myelodysplasia and/or therapy-related AML ( t -AML) as a late complication following cytotoxic therapy [1-3,5,6]. t -AML consists of 2 different syndromes: one with a long latency (5 to 7 years or more) observed following the administration of alkylating agents, which frequently show antecedent dysplastic changes and clonal abnormalities with loss of all or part of chromosome 5 or 7, or both.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary leukemia occurring after HSCT for AML is rare [41]. CHO et al reported a case of the second de novo acute myeloid leukemia following allogeneic HSCT for a first occurence of AML [42].…”
Section: Hematologic Malignanciesmentioning
confidence: 99%